Physical methods for the treatment of fever in critically ill patients: a randomized controlled trial - Salgado, Patrícia de Oliveira; Silva, Ludmila Christiane Rosa da; Silva, Priscila Marinho Aleixo; Chianca, Tânia Couto Machado (Revista da Escola de Enfermagem da USP, 2016)
OBJECTIVE To evaluate the effects of physical methods of reducing body temperature (ice pack and warm compression) in critically ill patients with fever. METHOD A randomized clinical trial involving 102 adult patients with tympanic temperature ≥ 38.3°C of an infectious focus, and randomized into three groups: Intervention I - ice pack associated with antipyretic; Intervention II - warm compress associated with antipyretic; and Control - antipyretic. Tympanic temperature was measured at 15 minute intervals for 3 hours. The effect of the interventions was evaluated through the Mann-Whitney test and Survival Analysis. "Effect size" calculation was carried out. RESULTS Patients in the intervention groups I and II presented greater reduction in body temperature. The group of patients receiving intervention I presented tympanic temperature below 38.3°C at 45 minutes of monitoring, while the value for control group was lower than 38.3°C starting at 60 minutes, and those who received intervention II had values lower than 38.3°C at 75 minutes of monitoring. CONCLUSION No statistically significant difference was found between the interventions, but with the intervention group I patients showed greater reduction in tympanic temperature compared to the other groups. Brazilian Registry of Clinical Trials: RBR-2k3kbq